A highly sensitive and quantitative detection method for bisphenol A (BPA) by competitive immunoassay based on surface-enhanced Raman spectroscopy. Issue 1 (2nd January 2018) - Lei, Zhang; Chen, Yingshan; Liu, Zhiwen; Ji, Wenjin; Zhao, Suqing
Abstract : Purpose: In this study, a highly sensitive and quantitative analysis method using surface-enhanced Raman scattering (SERS)-labeled immunoassay is adopted for bisphenol A bisphenol A (BPA) detection in water samples. Design/methodology/approach: Primarily, an excellent SERS immuno-nanoprobe is prepared, which relays on Au/Ag core-shell nanoparticles tagged 4-mercaptobenzoic acid (4MBA) and labeled with specific antibody against BPA. Second, the coating antigen of 4, 4-Bis(4-hydroxyphenol) valeric acid (BVA) coupling poly-L-lysine (PLL) conjugate (BVA-PLL) is fastened on the substrate. Based on competitive immunoassay, the antibody labeled on SERS immuno-nanoprobe will bind with the free BPA and BVA-PLL competitively. Findings: A calibration curve was obtained by plotting the intensity of SERS signal of 4MBA at 1007 cm −1 versus the concentration of BPA. The results indicated that the limit of detection (LOD) for BPA is 1 ng/mL and present a great capacity for higher sensitivity. Furthermore, the method was able to quantitatively detect BPA in water samples, which was validated by high performance liquid chromatography (HPLC). Originality/value: The method was developed based on competitive immunoassay, and the conjugate (BVA-PLL) was chosen as the coating antigen. Au/Ag core-shell nanoparticles played as the SERS active substrate and were labeled with Raman reporter. The value of this paper is supplying a wide potential for analysis of target analytes in the environmental monitoring and food safety.